2020
DOI: 10.24095/hpcdp.40.4.05
|View full text |Cite
|
Sign up to set email alerts
|

At-a-glance - Trends in emergency department visits for acetaminophen-related poisonings: 2011–2019

Abstract: We examined trends in emergency department (ED) presentation rates for acetaminophenrelated poisonings across Canada. A total of 27123 cases of poisoning were seen in the electronic Canadian Hospitals Injury Reporting and Prevention Program (eCHIRPP) sentinel sites between April 2011 and February 2019; of these, 13.7% were related to acetaminophen use. A significant decreasing trend for both sexes was observed for unintentional poisonings (males: −10.3%; females: −8.0%). For intentional poisonings, there was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Of these, female patients were more associated with acetaminophen poisonings along the entire period of study. This scenario has also been reported in the work of Kaur et al [18].…”
Section: Acetaminophen Poisoning Ratessupporting
confidence: 85%
“…Of these, female patients were more associated with acetaminophen poisonings along the entire period of study. This scenario has also been reported in the work of Kaur et al [18].…”
Section: Acetaminophen Poisoning Ratessupporting
confidence: 85%
“…Almost all RCTs and meta-analyses reported numbers of adverse events from paracetamol that were inferior to those of NSAIDs and comparable to those of placebo. However, reviews on long-term observational data reported increased cardiovascular, gastrointestinal, and renal adverse events during therapy with paracetamol, especially in the high dose range; cases of acute liver failure have been reported after accidental and unintentional overdose of paracetamol [ 10 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Acute liver failure is infrequent with an approximate incidence for all causes of 1/million/year and is declining [ 134 ].…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…However, reviews on long-term observational data reported increased cardiovascular, gastrointestinal, and renal adverse events during therapy with paracetamol, especially in the high dose range; cases of acute liver failure have been reported after accidental and unintentional overdose of paracetamol [ 10 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Acute liver failure is infrequent with an approximate incidence for all causes of 1/million/year and is declining [ 134 ]. In recent Canadian reports, the numbers of paracetamol ingestions reporting to the Emergency Department declined from April 2011 to February 2019 [ 134 ].…”
Section: Safety and Toxicitymentioning
confidence: 99%
See 2 more Smart Citations